Negative pole piece, battery cell and lithium ion battery
By setting a sub-region coating on the surface of the negative electrode sheet of the lithium-ion battery and adjusting the distribution of silicon material, the cyclic attenuation problem caused by volume expansion and contraction during the charging and discharging of the battery is solved, extending the cycle life of the battery cell and maintaining a high energy density.
Patent Information
- Application Number
- CN202311088916.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
The volume expansion and contraction of the negative electrode material of lithium-ion battery during charging and discharging leads to accelerated battery circulation attenuation, especially the local expansion in the central area of the large surface is the most serious.
A negative electrode sheet is designed, and the current collector surface is provided with a first regional coating and a second regional coating. The first regional coating is located in the central region and the second regional coating is located outside the first regional coating. Both contain active substances of silicon material, and the silicon material content in the second regional coating is higher than that of the first regional coating.
Through the difference in the distribution of silicon content at different locations, the local expansion of the large surface of the battery cell is alleviated, the cycle life of the battery cell is extended, and the high energy density of the battery cell is ensured.
Smart Images

Figure BDA0004419603360000051 
Figure BDA0004419603360000061 
Figure HDA0004419603370000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode sheet, a battery cell and a lithium-ion battery. Background Art
[0002] Silicon materials can be used as negative electrode materials for lithium-ion batteries, which can be alloyed with Li + Reaction contribution capacity, with high energy density, silicon negative electrode material has a theoretical specific capacity of up to 4200mAh / g, and is the most promising new generation of lithium-ion battery negative electrode material. In the process of manufacturing the negative electrode of a lithium-ion battery, a layer of foil (copper foil or aluminum foil) is used as a current collector, and active materials are coated on one or both sides of the current collector for lithium ion embedding or extraction to achieve the purpose of supplying energy. In the related art, active materials containing silicon materials are coated on one or both sides of the current collector. During the above coating, the content distribution of silicon materials is relatively uniform. However, during the operation of the silicon negative electrode, the embedding and extraction of lithium ions are accompanied by the expansion and contraction of the silicon negative electrode material, resulting in an increase of about 300% in the volume of the material during the charge and discharge process. In particular, the volume expansion of the central area of the pole piece is the most serious, causing the large central area of the lithium-ion battery to swell and accelerate the battery cycle decay. Summary of the invention
[0003] In view of this, the main purpose of the present application is to provide a negative electrode plate, a battery cell and a lithium-ion battery, which not only ensures the high energy density of the battery cell, but also effectively alleviates the local expansion of the battery cell in the central area of the large surface, thereby improving the cycle life of the battery cell.
[0004] To achieve the above-mentioned purpose of the invention, the first aspect of the present application provides a negative electrode plate, including: a current collector and a first region coating and a second region coating arranged on the surface of the current collector; the first region coating is located in the central region of the surface of the current collector, and the second region coating is located outside the first region coating, and the first region coating and the second region coating both include active substances containing silicon material, and the mass percentage of the silicon material in the second region coating is greater than the mass percentage of the silicon material in the first region coating.
[0005] Furthermore, the orthographic projection area of the first region coating on the surface of the current collector accounts for 40-70% of the total area of the current collector, and the orthographic projection area of the second region coating on the surface of the current collector accounts for 30-60% of the total area of the current collector.
[0006] Furthermore, in the first region coating, the mass percentage of silicon material in the active material is 3%-7%; in the second region coating, the mass percentage of silicon material in the active material is 10%-15%.
[0007] Furthermore, the first region coating is made of a first slurry consisting of an active substance containing silicon material, a conductive agent and a binder; the second region coating is made of a second slurry consisting of an active substance containing silicon material, a conductive agent and a binder.
[0008] Furthermore, the first slurry of the first region coating or the second slurry of the second region coating includes 90% to 95% by mass of active material, 1% to 2% by mass of conductive agent and 1% to 4.5% by mass of binder; the sum of the mass percentages of the active material, conductive agent and binder is 100%.
[0009] Furthermore, the silicon material includes one or more of SiOx material and Si / C material.
[0010] Furthermore, the active substance containing silicon material in the first region coating and the second region coating is a composite material of silicon material and graphite material.
[0011] Furthermore, the conductive agent is selected from one or more of carbon black, carbon nanotubes and graphene.
[0012] Furthermore, the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile and sodium alginate.
[0013] A second aspect of the present invention provides a battery cell, comprising a separator and a plurality of negative electrode plates provided by the first aspect.
[0014] The third aspect of the present invention provides a lithium-ion battery, comprising a shell and a battery cell, wherein the battery cell is placed in the shell, wherein the battery cell comprises a diaphragm and the negative electrode plate provided in the first aspect, and the diaphragm is provided on both sides of each electrode plate.
[0015] Compared with the prior art, this application has the following advantages:
[0016] In lithium-ion batteries, the volume expansion of the negative electrode during the charging process is the main reason for the expansion of the battery cell as a whole, especially the local expansion at the center of the large surface is the most serious. The negative electrode pole piece provided in the present application includes a current collector and a first region coating and a second region coating arranged on the surface of the current collector; the first region coating is located in the central area of the surface of the current collector, and the second region coating is located at the periphery of the first region coating. The first region coating and the second region coating both include active substances containing silicon materials, and the mass percentage of the silicon material in the second region coating is greater than the mass percentage of the silicon material in the first region coating. The present application sets up the negative electrode pole piece with the above-mentioned regional coating, and there are differences in the distribution of silicon content at different positions: that is, the silicon material content of the first region coating located in the central area (corresponding to the central position of the pole piece) is relatively low, which can alleviate the local expansion of the large surface of the battery cell to a certain extent, and the silicon material content of the second region coating located in the surrounding area is relatively high, so that the high gram capacity characteristics of the silicon material can be applied, thereby ensuring that the high energy density of the battery cell can be brought into play.
[0017] Other features and advantages of the present application will be described in detail through the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the coating structure of a negative electrode plate illustrated in this application.
[0019] Reference numerals: current collector 101 , first region coating A, second region coating B. DETAILED DESCRIPTION
[0020] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0021] In the description of the embodiments of the present application, if orientation descriptions are involved, the orientations or positional relationships indicated by "up", "down", "front", "back", "left", "right", etc. are based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or device referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the present application.
[0022] In the description of the embodiments of the present application, if a feature is referred to as being “set,” “fixed,” “connected,” or “installed” on another feature, it may be directly set, fixed, or connected to another feature, or it may be indirectly set, fixed, connected, or installed on another feature. In the description of the embodiments of the present application, if “several” is involved, it means more than one; if “multiple” is involved, it means more than two; if “greater than,” “less than,” or “exceeds” is involved, it should be understood as not including the number itself; if “above,” “below,” or “within” is involved, it should be understood as including the number itself. If “first” or “second” is involved, it should be understood as being used to distinguish technical features, and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0023] The distribution of silicon material in the pole piece will affect the electrochemical performance of the lithium-ion battery. The expansion of the area around the pole piece is small, and the expansion of the large surface center area is large. During the charge and discharge process, the huge change in the volume of the pole piece will cause the electrode to shatter, generate cracks, and expose new active sites, which will intensify the decomposition side reaction of the electrolyte on the negative electrode surface. The continuous consumption of electrolyte and active lithium will eventually lead to faster cycle decay of the battery. The inventor of this application has found that in the negative electrode pole piece obtained by regional coating, there are differences in the distribution of silicon content at different positions: the silicon material content in the central area is relatively low, which can alleviate the local expansion of the large surface center of the battery cell to a certain extent, and the silicon material content in the surrounding areas is relatively high, so that the high gram capacity characteristics of the silicon material can be applied, thereby ensuring that the high energy density of the battery cell can be brought into play.
[0024] Based on the above main ideas, the first aspect of the present application provides a negative electrode plate, including: a current collector and a first area coating and a second area coating arranged on the surface of the current collector; the first area coating is located in the central area of the surface of the current collector (corresponding to the central position of the electrode plate), and the second area coating is located on the periphery of the first area coating (surrounding area), and the first area coating and the second area coating both include active substances containing silicon materials, and the mass percentage of the silicon material in the second area coating is greater than the mass percentage of the silicon material in the first area coating.
[0025] In this application, the negative electrode plate is coated in different regions, the silicon material content in the central region of the plate is reduced, and the silicon material content in the surrounding region of the plate is increased. The low silicon content region is located in the center of the entire plate, and the area ratio of the central region to the surrounding region is appropriately adjusted, thereby alleviating the local expansion of the central position of the large surface of the battery cell to a certain extent.
[0026] Preferably, the orthographic projection area of the first region coating on the surface of the current collector accounts for 40-70% of the total area of the current collector, and the orthographic projection area of the second region coating on the surface of the current collector accounts for 30-60% of the total area of the current collector. The areas of the first region coating and the second region coating are further divided so that the first region coating just corresponds to the central expansion area of the battery cell.
[0027] In the present application, the first region coating is made of a first slurry consisting of an active substance containing silicon material, a conductive agent and a binder; the second region coating is made of a second slurry consisting of an active substance containing silicon material, a conductive agent and a binder.
[0028] Preferably, in the first region coating, the mass percentage of silicon material in the active material is 3%-7%, more preferably 3%-5%, and in the second region coating, the mass percentage of silicon material in the active material is 10%-15%, more preferably 10-12%. The gram capacity of silicon material is high, which can bring higher capacity to the battery cell, but the expansion problem of the material itself is serious, so the cycle storage performance is deteriorated. In order to take into account the disadvantages and advantages of silicon materials, the preferred mass percentage of the above silicon material in the active material of the first region coating or the active material of the second region coating is set.
[0029] In some embodiments, the active substance containing silicon material in the first region coating and the second region coating is a composite material of silicon material and graphite material. Preferably, in the active substance of the first region coating, the mass ratio of silicon material to graphite material is 3-7:93-97, and in the active substance of the second region coating, the mass ratio of silicon material to graphite material is 10-15:85-90.
[0030] In some embodiments, the first slurry of the first region coating or the second slurry of the second region coating includes 90% to 95% by mass of active material, for example, 90%, 91%, 93%, 94% or 95%, etc., and also includes 1% to 2% by mass of conductive agent, for example, 1%, 1.5% or 2%, etc., and 1% to 4.5% by mass of binder, for example, 1%, 2%, 3%, 4% or 4.5%, etc.; the sum of the mass percentages of the active material, conductive agent and binder is 100%.
[0031] In some embodiments, the silicon material includes one or more of SiOx materials and Si / C materials.
[0032] In some embodiments, the current collector may be a copper foil sheet, preferably with a thickness of 4.5-6.0 μm.
[0033] In the present application, the first region coating and the second region coating may be coated on one side of the current collector, or the first region coating and the second region coating may be coated on both sides of the current collector.
[0034] In this application, the thickness of the first region coating and the second region coating can be the same or different. Generally, compaction is used to characterize the thickness of the electrode, and the compaction range can be 1.5-1.6g / cm 3 , which are conventional parameters for negative electrode materials, and no distinction is made between the compaction of the coating in the first region and the compaction of the coating in the second region.
[0035] In some embodiments, the conductive agent is selected from one or more of carbon black, carbon nanotubes, and graphene.
[0036] In some embodiments, the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile and sodium alginate.
[0037] In the present application, the silicon material, graphite, conductive agent and adhesive in the first region coating and the second region coating can be the same or different, and there is no particular limitation in the present application.
[0038] In the present application, the coating and forming methods of the first region coating and the second region coating can refer to the prior art, for example, a slurry (such as the first slurry or the second slurry) containing an active material of silicon material, a conductive agent and a binder is disposed on the surface of the current collector by extrusion coating, and the solidified slurry is rolled in the thickness direction of the current collector to obtain the first region coating and the second region coating. The silicon material content in the first slurry and the second slurry is different.
[0039] The present application does not impose any restriction on the coating order of the first region coating and the second region coating. Each slurry (eg, the first slurry and the second slurry) may be coated on the current collector at the same time or sequentially.
[0040] A second aspect of the present application provides a battery cell, comprising a separator and a plurality of negative electrode plates provided in the first aspect.
[0041] A third aspect of the present application provides a lithium-ion battery, comprising a shell and a battery cell, wherein the battery cell is placed in the shell, wherein the battery cell comprises a diaphragm and the negative electrode plate provided in the first aspect, and the diaphragm is provided on both sides of each electrode plate.
[0042] The above-mentioned diaphragm is made of conventional materials, such as polypropylene film or polyethylene film, and the diaphragm materials on both sides of the pole piece can be the same material or different materials. Among them, the pole piece adopts the negative pole piece provided by the first aspect of the present application, so as to have all the advantages of the pole piece of the above-mentioned embodiment.
[0043] The following embodiments are used to illustrate the pole piece of the present application.
[0044] Example 1
[0045] like Figure 1 As shown, a negative electrode plate comprises: a current collector 101 and a first region coating 102 (abbreviated as A) and a second region coating 103 (abbreviated as B) arranged on the surface of the current collector;
[0046] The coating in the first region accounts for 40% of the area of the current collector surface (indicated by a), and the coating in the second region accounts for 60% of the area of the current collector surface (indicated by b);
[0047] In the first region coating, the mass percentage of silicon material in the active material is 3% (represented by x), and in the second region coating, the mass percentage of silicon material in the active material is 10% (represented by y); the total silicon material content in the negative electrode is ax+by.
[0048] The same silicon material, graphite, conductive agent and binder are selected in the first region coating and the second region coating. Among them, the mass percentage of negative electrode active material: conductive agent: binder is 96.5%: 1%: 2.5%; the negative electrode active material is a composite material of silicon material and graphite material (wherein the proportion of silicon material in each layer is different), the conductive agent is SP (superP), the binder is a composite of CMC (carboxymethyl cellulose) and SBR (styrene butadiene rubber), and the silicon material is pre-lithiated silicon oxide (Li-SiOx) and silane pyrolysis silicon carbon (Si / C).
[0049] Embodiment 2-6
[0050] The difference from Example 1 is that in the first region coating and the second region coating, the area ratio of each coating and the mass percentage of silicon material in each coating are different, as shown in Table 1 below.
[0051] Comparative Example 1
[0052] The difference from Example 1 is that the mass proportion of silicon material in the first region coating and the second region coating is the same, as shown in Table 1 below.
[0053] The negative electrode sheets obtained in the embodiment and the comparative example are used to make the battery cell according to the following process:
[0054] First, add a certain amount of N-methylpyrrolidone (NMP) to the ternary positive electrode material, carbon black and PVDF in a mass ratio of 92%:5%:3%, mix evenly, coat on aluminum foil, and dry to make a positive electrode. The negative electrode, separator, positive electrode and electrolyte are stacked in a dry room to prepare a lithium-ion battery cell. After the formation is completed, the room temperature cycle performance is tested after a certain number of cycles at 25°C 2.5-4.25V and 1C / 1C. The capacity retention rate is the ratio of the remaining capacity after 1000 cycles to the initial capacity of the first cycle.
[0055] The electrochemical properties of the batteries prepared from the materials of the examples and comparative examples of the present application are shown in Table 1 below:
[0056]
[0057]
[0058] According to the data in Table 1 above, compared with the negative electrode sheet with uniform silicon content distribution on the surface area of the current collector set in the prior art comparative example 1, the negative electrode sheet with non-uniform silicon content distribution on the surface area of the current collector set in Examples 1-4 of the present application has better electrochemical performance, higher capacity retention rate and cycle number. Compared with Example 1, the area ratio of A:B in Example 5 is not within the preferred range of the present invention, resulting in a large expansion in the middle of the battery cell, and the capacity decays faster during the battery cell cycle. The silicon content ratio of x:y in Example 6 is not within the preferred range of the present invention, resulting in a certain degree of swelling in the center of the battery cell, and the capacity decays faster during the battery cell cycle.
[0059] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the present application, and are not intended to limit the implementation methods of the present application. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solutions of the present application are within the spirit scope covered by the present application.
Claims
1. A negative electrode plate, characterized in that: include: A current collector and a first region coating and a second region coating disposed on the surface of the current collector; The first region coating is located in the central region of the current collector surface, and the second region coating is located at the periphery of the first region coating. Both the first region coating and the second region coating include active substances containing silicon material, and the mass percentage of the silicon material in the second region coating is greater than the mass percentage of the silicon material in the first region coating.
2. The pole piece according to claim 1, characterized in that: The orthographic projection area of the first region coating on the surface of the current collector accounts for 40-70% of the total area of the current collector, and the orthographic projection area of the second region coating on the surface of the current collector accounts for 30-60% of the total area of the current collector.
3. The pole piece according to claim 1, characterized in that: In the first region coating, the mass percentage of silicon material in the active material is 3%-7%; in the second region coating, the mass percentage of silicon material in the active material is 10%-15%.
4. The pole piece according to any one of claims 1 to 3, characterized in that: The first region coating is made of a first slurry consisting of an active substance containing silicon material, a conductive agent and a binder; the second region coating is made of a second slurry consisting of an active substance containing silicon material, a conductive agent and a binder.
5. The pole piece according to claim 4, characterized in that: The first slurry of the first region coating or the second slurry of the second region coating includes 90% to 95% by mass of active material, 1% to 2% by mass of conductive agent and 1% to 4.5% by mass of binder; the sum of the mass percentages of the active material, conductive agent and binder is 100%.
6. The pole piece according to any one of claims 1 to 3, characterized in that: The active material in the first region coating and the second region coating is a composite material of silicon material and graphite material; and / or, The silicon material includes one or more of SiOx material and Si / C material.
7. The pole piece according to claim 4, characterized in that: The conductive agent is selected from one or more of carbon black, carbon nanotubes and graphene.
8. The pole piece according to claim 4, characterized in that: The binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile and sodium alginate.
9. A battery cell, characterized in that: It comprises a separator and a plurality of negative electrode sheets as described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It comprises a shell and a battery cell, wherein the battery cell is placed in the shell; wherein the battery cell comprises a diaphragm and a plurality of negative electrode plates as described in any one of claims 1 to 8, and the diaphragm is provided on both sides of each of the electrode plates.